2023
DOI: 10.3389/fimmu.2022.1065379
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of ERCC1 in early-stage and advanced cervical cancer: From experiments to clinical applications

Abstract: Cervical cancer is a public health problem of extensive clinical importance. Excision repair cross-complementation group 1 (ERCC1) was found to be a promising biomarker of cervical cancer over the years. At present, there is no relevant review article that summarizes such evidence. In this review, nineteen eligible studies were included for evaluation and data extraction. Based on the data from clinical and experimental studies, ERCC1 plays a key role in the progression of carcinoma of the uterine cervix and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Nevertheless, the use of these indicators might enhance treatment outcomes and facilitate the development of novel targeted medicines. As an example of these previous statements, a study by Du [30] underlined that ERCC1 has been identified as a very promising biomarker for cervical cancer. Analysis of ERCC1 polymorphism suggests that it might serve as a valuable tool for predicting the likelihood of developing cervical cancer and the potentially hazardous side effects of therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the use of these indicators might enhance treatment outcomes and facilitate the development of novel targeted medicines. As an example of these previous statements, a study by Du [30] underlined that ERCC1 has been identified as a very promising biomarker for cervical cancer. Analysis of ERCC1 polymorphism suggests that it might serve as a valuable tool for predicting the likelihood of developing cervical cancer and the potentially hazardous side effects of therapy.…”
Section: Discussionmentioning
confidence: 96%
“…We used Haploview version 4.2 to choose the Haplotype tagging SNPs. They were chosen based on our previous research about lung cancer prognosis [9,34], and these genes were also associated with the outcome of multiple cancers [35,36]. And all the selected SNPs must satisfy the condition that the minor allele frequency (MAF) > 0.05 in the HapMap CHB population.…”
Section: Snp Selecting Dna Extraction and Genotypingmentioning
confidence: 99%
“…They crosslink DNA molecules, causing extensive DNA damage and triggering apoptosis in cancer cells. However, in many cancer cells, the NER pathway is overactive due to the overexpression of ERCC1, which can diminish the therapeutic effectiveness of cisplatin and even lead to drug resistance [165][166][167][168]. Therefore, the design of selective NER/ERCC1 inhibitors holds promise in the enhancement of the efficacy of platinum-based treatments.…”
Section: Ercc1 Inhibitorsmentioning
confidence: 99%